2013
DOI: 10.1021/ie302122s
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Studies of CO2 Removal from Precombustion Syngas through Pressure Swing Membrane Absorption Process with Ionic Liquid as Absorbent

Abstract: Using 1-butyl-3-methylimidazolium dicyanamide ([bmim]­[DCA]) as the absorbent and either hydrophobized porous ceramic tubule or hydrophobized polyether ether ketone (PEEK)-based porous hollow fiber membranes, we have carried out preliminary studies for CO2 removal from simulated precombustion syngas by a pressure swing membrane absorption process. We have used He as a surrogate for H2 (40% CO2 rest He) up to a temperature of 100 °C and a pressure of 250 psig. A novel 5-valve system was designed to improve prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 32 publications
2
35
0
Order By: Relevance
“…More recently, [26] and yttrium-stabilized zirconia (YSZ) [27] were applied with success as a practicable alternative hollow fiber in the advanced field of "water desalination" via membrane distillation process. In this light, Jie et al [34] investigated silane-coated hydrophobic porous ceramic tubule in comparison with hydrophobized polyether ether ketone (PEEK)-based porous hollow fiber membranes using 1-butyl-3-methylimidazolium dicyanamide ([bmim][DCA]) as pure ionic liquid absorbent for CO 2 removal from simulated precombustion syngas by a pressure swing membrane absorption (PSMAB) process, and the authors suggest that there is significant potential for future research in the area of ceramic module that show stable separation results under high temperature. In particular, Chau et al [35] suggested that the ceramic system produced poor product qualities with pure ionic liquid [bmim][DCA] due to large tube side gas volume and small gas-liquid contacting area.…”
mentioning
confidence: 95%
“…More recently, [26] and yttrium-stabilized zirconia (YSZ) [27] were applied with success as a practicable alternative hollow fiber in the advanced field of "water desalination" via membrane distillation process. In this light, Jie et al [34] investigated silane-coated hydrophobic porous ceramic tubule in comparison with hydrophobized polyether ether ketone (PEEK)-based porous hollow fiber membranes using 1-butyl-3-methylimidazolium dicyanamide ([bmim][DCA]) as pure ionic liquid absorbent for CO 2 removal from simulated precombustion syngas by a pressure swing membrane absorption (PSMAB) process, and the authors suggest that there is significant potential for future research in the area of ceramic module that show stable separation results under high temperature. In particular, Chau et al [35] suggested that the ceramic system produced poor product qualities with pure ionic liquid [bmim][DCA] due to large tube side gas volume and small gas-liquid contacting area.…”
mentioning
confidence: 95%
“…In the module used here, the shell-side liquid amine thickness between the contiguous hollow fibers is considerable resulting in the not-so-sharp-a-rise in the outlet CO 2 concentration. [27,29].…”
Section: Resultsmentioning
confidence: 99%
“…As a result the gas located at the furthest point from the feed gas entrance is purer in helium than at any other locations since the absorbent is CO 2 -selective. This 5-valve based PSMAB system was first proposed by Jie et al [13]. The cycle time varies between 75 to 150 s; a typical distribution of cycle time for each step in second for the 6 steps is as follows: 10; 60; 1; 3; 60; 2.…”
Section: Method: Psmab Process Description Based On 5-valvesmentioning
confidence: 99%
“…The cycle time varies between 75 to 150 s; a typical distribution of cycle time for each step in second for the 6 steps is as follows: 10; 60; 1; 3; 60; 2. Generally one small membrane module was used to study the process [13,14]. Here we have two membrane modules to increase the membrane surface area.…”
Section: Method: Psmab Process Description Based On 5-valvesmentioning
confidence: 99%
See 1 more Smart Citation